2018
DOI: 10.3389/fnhum.2018.00017
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating Explicit and Implicit Timing in Parkinson’s Disease Patients: Evidence from Bisection and Foreperiod Tasks

Abstract: A consistent body of literature reported that Parkinson’s disease (PD) is marked by severe deficits in temporal processing. However, the exact nature of timing problems in PD patients is still elusive. In particular, what remains unclear is whether the temporal dysfunction observed in PD patients regards explicit and/or implicit timing. Explicit timing tasks require participants to attend to the duration of the stimulus, whereas in implicit timing tasks no explicit instruction to process time is received but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 78 publications
(137 reference statements)
7
22
0
Order By: Relevance
“…This statement holds even when cognitive factors, such as attention and working memory, were minimized in the tasks. Therefore, these results seem to confirm past studies stating differences in explicit and implicit mechanisms [1,[7][8][9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This statement holds even when cognitive factors, such as attention and working memory, were minimized in the tasks. Therefore, these results seem to confirm past studies stating differences in explicit and implicit mechanisms [1,[7][8][9].…”
Section: Discussionsupporting
confidence: 91%
“…Of the many brain areas known to be involved in the processing of time [3][4][5], the basal ganglia are considered the central hypothetical internal clock [3,6]. Similarly, Mioni and colleagues [7] recently showed that while patients with Parkinson's disease (PD), who suffer degeneration in the dopaminergic system involving the basal ganglia, perceived durations to be shorter than they actually were in the explicit task, they had intact temporal cognition in the implicit task.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in Triviño et al (2010) we found that the group with lesions in right basal ganglia did not show any impairment of the three temporal preparation effects compared to a group of healthy participants. Altogether, these results suggest that subcortical structures like the basal ganglia might not be essential for the temporal preparation effects studied here, as in the study performed by Mioni et al (2018) with Parkinson's disease. This finding contrasts with a recent study showing that temporal preparation based on rhythms (i.e., a process of temporal preparation that is highly automatic, similarly to sequential effects; Correa et al, 2014;Cutanda, Correa & Sanabria, 2015;Triviño et al, 2011) was impaired in Parkinson's disease, which can be considered a model of basal ganglia dysfunction (Breska & Ivry, 2018).…”
Section: Discussionsupporting
confidence: 48%
“…The neural basis of sequential effects, however, is largely unknown. So far, we know that Sequential effects do not rely on either the prefrontal lobes (they are preserved after both left and right prefrontal lesions; Triviño et al, 2011;Triviño et al, 2010) or the basal ganglia (they have been seen preserved in patients with Parkinson's Disease; Mioni et al, 2018).…”
mentioning
confidence: 99%
“…Striatal dysfunction was found during the two phases, but the working memory capacity composed by the prefrontal dorsolateral cortex (DLPFC), parietal cortex and cerebellum were only disturbed during the coding of the time intervals. Despite all the researches carried out in this field, there are still doubts about the exact nature of TP problems in PD individuals, for instance, Mioni et al [ 144 ] investigated TP in PD, comparing 20 PD participants and 20 control individuals without the disease in explicit (bisection task) and implicit (foreperiod task) timing tasks. The results showed that PD participants presented a preserved ability to perceive the implicit time, but underestimated the explicit one, besides a higher variability of timing when compared to the controls.…”
Section: Discussionmentioning
confidence: 99%